2021
DOI: 10.1007/s10479-021-04129-6
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain technology’s impact on supply chain integration and sustainable supply chain performance: evidence from the automotive industry

Abstract: The study investigates the relationship between the information and communication-enabled supply chain integration (SCI) and sustainable supply chain performance (SSCP). Moreover, to the best of our knowledge, there is no empirical evidence on the impact of blockchain technologies (BT) on the SSCP. Therefore, the primary aim of this study is to assess the relationship between BT and SSCP. More specifically, the study was conducted to examine the direct influence of BT on SCI and SSCP and the interactive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(94 citation statements)
references
References 115 publications
(170 reference statements)
3
88
0
3
Order By: Relevance
“…Last by not least, in our final reflection of this review, we stumbled upon the greatly astonishing state of sustainable finance, wherein the application and discussion of new-age technologies in sustainable finance research is almost virtually non-existent despite its omnipresence in other fields such as business sustainability (Sivarajah et el., 2020 ), sustainable automotive (Kamble et al, 2021 ) and humanitarian supply chain (Bag et al, 2020 ), sustainable logistics service quality (Gupta et al, 2021 ), and sustainability marketing (Bolton, 2021 ). In essence, new-age technologies refer to new technologies that emerge as new industrial revolutions surface, with technologies such as artificial intelligence, blockchain, internet of things, and machine learning being born out of the recent fourth industrial revolution (IR4.0) (Gupta et al, 2020 ).…”
Section: Forging the Way Forwardmentioning
confidence: 99%
“…Last by not least, in our final reflection of this review, we stumbled upon the greatly astonishing state of sustainable finance, wherein the application and discussion of new-age technologies in sustainable finance research is almost virtually non-existent despite its omnipresence in other fields such as business sustainability (Sivarajah et el., 2020 ), sustainable automotive (Kamble et al, 2021 ) and humanitarian supply chain (Bag et al, 2020 ), sustainable logistics service quality (Gupta et al, 2021 ), and sustainability marketing (Bolton, 2021 ). In essence, new-age technologies refer to new technologies that emerge as new industrial revolutions surface, with technologies such as artificial intelligence, blockchain, internet of things, and machine learning being born out of the recent fourth industrial revolution (IR4.0) (Gupta et al, 2020 ).…”
Section: Forging the Way Forwardmentioning
confidence: 99%
“…[ [44][45][46][47] Quality and Compliance Issues Procuring a replacement for defective parts is a long-drawn and uncomfortable process. [48][49][50][51] Inevitable disruptions LEAN "on-demand" manufacturing falls flat in a situation where natural disasters and socio-economic problems are common. For example, Japan (frequently affected by earthquakes) has outsourced most of its supply chain logistics to other countries.…”
Section: Issue Description Referencesmentioning
confidence: 99%
“…There is a need for organizations to focus on these issues to improve overall operational efficiency. Kamble et al, (2021) reviewed blockchain technology's impact on the automotive supply chain and summarized the relationship between blockchain and sustainable supply performance [51]. Khanfar et al, (2021) reviewed the application of blockchain technology in manufacturing and suggested opportunities for new directions of research [52].…”
Section: Research Gapmentioning
confidence: 99%
“…19. Kamble et al (2021b) The main objective of this study is to investigate the effect of the information-enabled supply chain on its sustainable performance.…”
Section: Prototypical Developmentmentioning
confidence: 99%